Challenges in recognizing urothelial carcinoma in situ with plasmacytoid features by urinary cytology. Issue 10 (26th April 2021) - Allison, Derek B.
Abstract : The first study reporting the urinary cytology findings in patients with the recently described urothelial carcinoma in situ with plasmacytoid features (P‐CIS) suggests that variant morphologic findings of P‐CIS are subtle and often do not meet the Paris System for Reporting Urinary Cytology criteria for high‐grade urothelial carcinoma.